Detection Of F-Score Model On Fraudulent Financial Reporting With Fraud Pentagon Theory - Oka Septa Tinambunan; Indira Januarti (Jurnal Reviu Akuntansi dan Keuangan, 2022)
The purpose of this study is to investigate the impact of fraud Pentagon theory on the detection of fraudulent financial reporting in the banking sector from 2015-2019. Independent variable is proxies from fraud pentagon theory which are financial target, financial stability, external pressure, ineffective of monitoring, changes in auditor, changes in directors, and frequent number of CEO’s pictures while dependent variable is fraudulent financial reporting. The population of this study is the entire banking sector listed on the Indonesia Stock Exchange since 2015-2019. Total sample used is 180 samples. The statistical technique used in this research is panel data with multiple regression analysis method with PLS (Partial Least Square) Smart PLS 3.0 software. The result this study shows financial stability and ineffective monitoring meeting have an effect in detecting indication of financial reporting. The results of this study can be used by users of financial statements as a reference in detecting indications of fraudulent financial reporting. The contribution of this research to stakeholders, including management and policy maker in terms of fraud detection as one of the pillars of an anti-fraud strategy using ratios from financial statements.